Calcium decoration of boron nitride nanotubes with vacancy defects as potential hydrogen storage materials: A first-principles investigation. (March 2021) - Ma, Liang-Cai; Sun, Ya-Ru; Wang, Li-Chun; Ma, Ling; Zhang, Jian-Min
Graphical abstract: Six H2 molecules can be adsorbed on each of the Ca atom of 8Ca/BNNT-VB and 8Ca/BNNT-VBN substrates. The calculated average adsorption energy is 0.206 and 0.207 eV/H2 in 48H2 +8Ca/BNNT-VB and 48H2 +8Ca/BNNT-VBN complexes, respectively. And the corresponding hydrogen gravimetric densities in the 8Ca/BNNT-VB and 8Ca/BNNT-VBN systems are 6.4 wt.% and 6.9 wt.%, respectively, Pictogram Highlights: Ca-decoration significantly improved hydrogen storage capacity of defective BNNT. Six H2 molecules can be absorbed per Ca atom with the adsorption energy of ∼0.2 eV/H2. The polarization mechanism and orbital hybridization are involved in H2 adsorption. The hydrogen gravimetric densities are estimated to be larger than 6.4 wt.%. Abstract: Hydrogen adsorption and storage performance of Ca-decorated boron nitride nanotubes (BNNTs) with vacancy defects are investigated theoretically using the first-principle calculation. Three types of experimentally available defects, B monovacancy (VB ), N monovacancy (VN ) and B–N divacancy (VNB ), are considered. The Ca atom prefers to reside on the vacancy site of BNNTs-VB and BNNTs-VBN without the problem of aggregation. The H2 adsorption results indicate that six H2 can be adsorbed by a Ca atom with the average adsorption energy slightly larger than 0.20 eV/H2 . The hydrogen gravimetric density is 6.4 wt.% and 6.9 wt.% for 8Ca/BNNT-VB and 8Ca/BNNT-VBN systems, respectively. The polarization interaction and the weaker orbitals hybridization between Ca and H2 are responsible for the hydrogen adsorption. The stability of the H2 adsorbed complexes is also investigated by considering the temperature and pressure. The results indicate that the H2 adsorbed structures of Ca-decorated BNNSs with VB and VBN defects are stable at room temperature under commonly used mild pressure.